Operando generated ordered heterogeneous catalyst for the selective conversion of CO2 to methanol - Cherevotan, Arjun; Raj, Jithu; Dheer, Lakshay; Roy, Soumyabrata; Sarkar, Shreya; Das, Risov; Vinod, Chathakudath P.; Xu, Shaojun; Wells, Peter; Waghmare, V, Umesh; Peter, Sebastian C. (ACS Energy Letters, 2021)
The discovery of new materials for efficient transformation of carbon dioxide (CO2) into desired fuel can revolutionize large-scale renewable energy storage and mitigate environmental damage due to carbon emissions. In this work, we discovered an operando generated stable Ni-In kinetic phase that selectively converts CO2 to methanol (CTM) at low pressure compared to the state-of-the-art materials. The catalytic nature of a well-known methanation catalyst, nickel, has been tuned with the introduction of inactive indium, which enhances the CTM process. The remarkable change in the mechanistic pathways toward methanol production has been mapped by operando diffuse reflectance infrared Fourier transform spectroscopy analysis, corroborated by first-principles calculations. The ordered arrangement and pronounced electronegativity difference between metals are attributed to the complete shift in mechanism. The approach and findings of this work provide a unique advance toward the next-generation catalyst discovery for going beyond the state-of-the-art in CO2 reduction technologies.

Unveiling the roles of lattice strain and descriptor species on pt-like oxygen reduction activity in Pd-Bi catalysts - Sarkar, Shreya; Ramarao, S. D.; Das, Tisita; Das, Risov; Vinod, C. P.; Chakraborty, Sudip; Peter, Sebastian C. (ACS Catalysis, 2021)
A facile non-template-assisted mechanical ball milling technique was employed to generate a PdBi alloy catalyst. The induced lattice strain upon the milling time caused a shift of the d-band center, thereby enhancing the oxygen reduction reaction (ORR) catalytic activity. Additionally, the Pd-O reduction potential and adsorbed OH coverage used as descriptors stipulated the cause of the enhanced ORR activity upon the increased milling interval. Redox properties of surface Pd are directly correlated with a positive shift in the Pd-O reduction potential and OH surface coverage. Hence, by deconvoluting the lattice strain and the role of the descriptor species we achieved a catalyst system with a specific activity 5.4X higher than that of commercial Pt/C, as well as an improved durability. The experimental observation is well-corroborated by a theoretical simulation done by inducing strain to the system externally.
Keywords: charge-transfer; electrocatalysis; fuel cell; Lattice strain; oxygen reduction; Pt-like activity

Green transformation of CO2 to ethanol using water and sunlight by the combined effect of naturally abundant red phosphorus and Bi2MoO6 - Das, Risov; Das, Kousik; Ray, Bitan; Vinod, Chathakudath P.; Peter, Sebastian C. (Energy & Environmental Science, 2022)
Direct photocatalytic conversion of CO2 to ethanol remains a scientific challenge because of the sluggish kinetics of C-C coupling and complex multielectron transfer processes. To achieve a green transformation of CO2 to C1+ products using naturally abundant sunlight and water requires the smart design of an efficient catalyst by selecting the right combination of atoms either in elemental or in compound form. Herein, we report a composite photocatalyst composed of earth abundant red phosphorus (RP) in nano-sheet morphology decorated with Bi2MoO6 nano-particles. The composite synthesised by a facile ultrasonication method produces 51.8 mu mol g(-1) h(-1) of ethanol from CO2. The ability of RP for the conversion of CO2 to C1 has been altered by the introduction of Bi2MoO6. In situ Diffuse Reflectance Infrared Fourier Transform Spectroscopy (DRIFTS) and Kinetic Isotopic Effect (KIE) analysis shed light on the mechanistic pathway, which propose that the presence of Bi-Mo dual sites play a crucial role in the C-C coupling toward the formation of ethanol. Spectroscopic evidence and isotope labeling experiments suggest that the intermediate OCH3* is the key active species for ethanol formation via self-coupling followed by proton transfer.

Morphology-tuned Pt3Ge accelerates water dissociation to industrial-standard hydrogen production over a wide pH range - Mondal, Soumi; Sarkar, Shreya; Bagchi, Debabrata; Das, Tisita; Das, Risov; Singh, Ashutosh Kumar; Prasanna, Ponnappa Kechanda; Vinod, C. P.; Chakraborty, Sudip; Peter, Sebastian C. (Advanced Materials, 2022)
The discovery of novel materials for industrial-standard hydrogen production is the present need considering the global energy infrastructure. A novel electrocatalyst, Pt3Ge, which is engineered with a desired crystallographic facet (202), accelerates hydrogen production by water electrolysis, and records industrially desired operational stability compared to the commercial catalyst platinum is introduced. Pt3Ge-(202) exhibits low overpotential of 21.7 mV (24.6 mV for Pt/C) and 92 mV for 10 and 200 mA cm(-2) current density, respectively in 0.5 m H2SO4. It also exhibits remarkable stability of 15 000 accelerated degradation tests cycles (5000 for Pt/C) and exceptional durability of 500 h (@10 mA cm(-2)) in acidic media. Pt3Ge-(202) also displays low overpotential of 96 mV for 10 mA cm(-2) current density in the alkaline medium, rationalizing its hydrogen production ability over a wide pH range required commercial operations. Long-term durability (>75 h in alkaline media) with the industrial level current density (>500 mA cm(-2)) has been demonstrated by utilizing the electrochemical flow reactor. The driving force behind this stupendous performance of Pt3Ge-(202) has been envisaged by mapping the reaction mechanism, active sites, and charge-transfer kinetics via controlled electrochemical experiments, ex situ X-ray photoelectron spectroscopy, in situ infrared spectroscopy, and in situ X-ray absorption spectroscopy further corroborated by first principles calculations.
Keywords: Electrochemistry; hydrogen production; intermetallics; water electrolysis

Noble-metal-free heterojunction photocatalyst for selective CO2 reduction to methane upon induced strain relaxation - Das, Risov; Sarkar, Shreya; Kumar, Ritesh; Ramarao, Seethiraju D.; Cherevotan, Arjun; Jasil, Mohammed; Vinod, Chathakudath P.; Singh, Abhishek Kumar; Peter, Sebastian C. (ACS Catalysis, 2022)
Sunlight-driven CO2 hydrogenation has drawn tremendous attention. However, selective CH4 formation via CO2 photoreduction is very challenging. Herein, we report a metal oxide semiconductor heterojunction consisting of BiVO4 and WO3 as a photocatalyst for the efficient conversion of carbon dioxide (CO2) selectively to methane (105 mu mol g(-1) h(-1)) under visible light in the absence of a sacrificial agent. Wise selection of the reaction medium and the strategically tuned heterojunction upon strain relaxation suppresses the competitive hydrogen generation reaction. The detailed photophysical, photoelectrochemical, and X-ray absorption spectroscopy studies pointed to the Z-scheme mechanism of electron transfer, which favors superior electron and hole separation compared to the individual components of the composite catalyst and other well-known photocatalysts reported for CO2 reduction. The observations are further corroborated by experimental diffuse reflectance infrared Fourier transform spectroscopy and theoretical density-functional theory calculations, which reveal that the heterojunction has a lower free-energy barrier for CO2 conversion to CH4 due to the larger stabilization of the *CH2O intermediate on the strain-relaxed heterojunction surface, in comparison to the pristine BiVO4 surface. The present work provides fundamental insights for constructing high-performance heterojunction photocatalysts for the selective conversion of CO2 to desired chemicals and fuels.
Keywords: CO2 reduction; heterostructure; methane; Photocatalysis; Z-scheme

Intrinsic charge polarization in Bi19S27Cl3 nanorods promotes selective C-C coupling reaction during photoreduction of CO2 to ethanol - Das, Kousik; Das, Risov; Riyaz, Mohd; Parui, Arko; Bagchi, Debabrata; Singh, Ashutosh Kumar; Singh, Abhishek Kumar; Vinod, Chathakudath P.; Peter, Sebastian C. (Advanced Materials, 2023)
Obtaining multi-carbon products via CO2 photoreduction is a major catalytic challenge involving multielectron-mediated C-C bond formation. Complex design of multicomponent interfaces that are exploited to achieve this chemical transformation, often leads to untraceable deleterious changes in the interfacial chemical environment affecting CO2 conversion efficiency and product selectivity. Alternatively, robust metal centers having asymmetric charge distribution can effectuate C-C coupling reaction through the stabilization of intermediates, for desired product selectivity. However, generating inherent charge distribution in a single component catalyst is a difficult material design challenge. Here, a novel photocatalyst, Bi19S27Cl3, is presented which selectively converts CO2 to a C-2 product, ethanol, in high yield under visible light irradiation. Structural analysis through transmission electron microscopy, X-ray diffraction, X-ray photoelectron spectroscopy, and X-ray absorption spectroscopy reveals the presence of charge polarized bismuth centers in Bi19S27Cl3. The intrinsic electric field induced by charge polarized bismuth centers renders better separation efficiency of photogenerated electron-hole pair. Furthermore, charge polarized centers yield better adsorption of CO* intermediate and accelerate the rate determining C-C coupling step through the formation of OCCOH intermediate. Formation of these intermediates is experimentally mapped by in situ Fourier-transform infrared spectroscopy and further confirmed by theoretical calculation.
Keywords: C-C coupling; charge polarization; CO2 reduction; Ethanol; Photocatalysis

Wurtzite CuGaS2 with an in-situ-formed CuO layer photocatalyzes CO2 conversion to ethylene with high selectivity - Chakraborty, Subhajit; Das, Risov; Riyaz, Mohd; Das, Kousik; Singh, Ashutosh Kumar; Bagchi, Debabrata; Vinod, Chathakudath P.; Peter, Sebastian C. (Angewandte chemie-international edition, 2023)
We present surface reconstruction-induced C-C coupling whereby CO2 is converted into ethylene. The wurtzite phase of CuGaS2. undergoes in situ surface reconstruction, leading to the formation of a thin CuO layer over the pristine catalyst, which facilitates selective conversion of CO2 to ethylene (C2H4). Upon illumination, the catalyst efficiently converts CO2 to C2H4 with 75.1 % selectivity (92.7 % selectivity in terms of R-electron) and a 20.6 mu mol g(-1) h(-1) evolution rate. Subsequent spectroscopic and microscopic studies supported by theoretical analysis revealed operando-generated Cu2+, with the assistance of existing Cu+, functioning as an anchor for the generated *CO and thereby facilitating C-C coupling. This study demonstrates strain-induced in situ surface reconstruction leading to heterojunction formation, which finetunes the oxidation state of Cu and modulates the CO2 reduction reaction pathway to selective formation of ethylene.
Keywords: C-C coupling; charge polarization; CO2 reduction; Photocatalysis

Dopant and exfoliation induced simultaneous modification of charge density and C―C coupling sites for efficient CO2 photoreduction to ethylene - Das, Kousik; Chakraborty, Subhajit; Kediya, Siddhi; Singh, Ashutosh Kumar; Das, Risov; Mondal, Soumi; Riyaz, Mohd; Goud, Devender; Dutta, Nilutpal; Vinod, Chathakudath P.; Peter, Sebastian C. (Angewandte Chemie-International Edition, 2025)
The photochemical conversion of CO2 into C2+ products has emerged as an attractive method for synthesizing valuable chemicals and fuels using abundant solar energy. However, the challenge lies in enhancing the efficiency and selectivity of C2+ product formation. In this study, we employed a heteroatom doping strategy to optimize the photocatalytic parameters and achieve excellent efficiency and selectivity in the photocatalytic CO2 reduction to C2+ product formation. Our experimental analysis revealed that the local electronic structure of the catalyst, modified by In-doping, enables enhanced efficiency. Additionally, the incorporation of Cu facilitates the coupling of C1 intermediates, resulting in excellent selectivity towards C2+ products. The CO2 reduction performance is further enhanced through exfoliation, which increases the exposure of active sites and extends the charge carrier lifetime by reducing the charge diffusion length. We report that the rate of formation of C2H4 reached 54.3 mu molh(-1)g(-1) with an outstanding selectivity of 91% over the exfoliated CuIn-doped AgBiP2S6 catalyst. By elucidating the role of heteroatom doping and exfoliation in enhancing both the efficiency and selectivity of C2+ product formation, our study contributes to advancing the development of sustainable and efficient photocatalytic CO2 conversion technologies.
Keywords: C & horbar; C coupling; CO2 reduction; Doping; Exfoliation; Photocatalysis